Measurements of natural ice nucleating particles in Beijing in the spring of 2017. (1st March 2019) - Che, Yunfei; Dang, Juan; Fang, Wen; Shen, Xiaojing; Sun, Junying; Chen, Yue; Qian, Yao
Abstract: The ice nucleating particles (INPs) in the ambient air in Beijing during the spring of 2017 were observed using an improved 5-L version of Bigg's mixing cloud chamber. The characteristics of the diurnal INPs concentrations are analyzed and compared with measurements made in 1963, 1995 and 1996. The particle number size distribution was also measured simultaneously. The correlation between the concentration of INPs and the aerosol number concentration in different size ranges is discussed. Moreover, the relationship between the concentration of INPs and different meteorological factors, such as wind speed, air pressure, temperature, humidity and weather conditions, are analyzed. From the results of observation, in general, the concentrations of INPs at −20 °C, −25 °C and −30 °C temperatures trend with each other on a day to day basis, although there are slight differences in some cases at −20 °C. As the activation temperatures decrease by 5 °C, the concentration of INPs increases by about one order of magnitude. The concentration of INPs increases significantly when air pollution is severe, but the specific relationship between INPs and pollution needed to be verified in the follow-up work, which is related to the source of pollution and the aerosol components. Compared with historical experimental data, interpreting trends using short sampling periods in individual years over decadal time frames, the average concentrations of INPs in Beijing increased by approximately 15 times from 1963 to 1996, but in the past 20 years, the concentration of INPs has decreased significantly. For aerosols with particle size that exceeds 0.5 μm, the correlation coefficient between aerosol number concentration and INPs increases significantly with increasing aerosol particle size; however, it tends to stabilize at approximately 0.6 for aerosol particles larger than approximately 2 μm. A comparison with meteorological parameters shows that the concentration of INPs is inversely correlated with wind speed, and displays a positive correlation with relative humidity. These results indicate that conditions that favor dispersion lead to reduced concentrations of INPs. Highlights: Observe ice nucleating particles in Beijing using an improved Bigg's mixing cloud chamber. Compare ice nucleating particles with particle number size distribution. Analyze the relationship between ice nucleating particles with pollution. Comparison with historical, analyze the changes of ice nucleating particles in Beijing.